The United Nations Women and Gender Equality in Nigeria:: Challenges and Prospects - Ayodeji, Bello Lateefat; Ade-Ibijola, Aderemi Opeyemi (African Journal of Stability and Development (AJSD), 2022)
Over the years, the United Nations made several attempts to prioritise gender equality through the establishment of international treaties, conventions, and creation of entities dedicated to address the needs of women. The UN Women is one of such laudable initiatives. It is in this connection that this paper examined the challenges of promoting gender equality in Nigeria, focusing on the agenda set by UN Women. Specifically, the paper looks at Nigeria’s progress so far in attaining the four target areas of the UN Women in Nigeria. The target areas include: Peace, Security and Humanitarian Action, Economic Empowerment and Resilience, Leadership and Political Participation, and Ending Violence against Women. The paper leveraged the critical and liberal feminist theories to analyse gender equality issues and the challenges posed to the UN women efforts in promoting gender equality in Nigeria. The paper argues that Nigeria has made some progress in the target areas of the UN Women through the ratification of international treaties, policy formulation, and creation of agencies. The UN women has also demonstrated commitment to its aim of promoting gender equality in Nigeria in its four thematic areas of engagement through campaigns and advocacy, capacity-building, partnerships and strategic alliances; service delivery and improving access to services. However, there are challenges that hinder the promotion of gender equality in the country. These challenges include: the Nigerian law, insecurity, the political terrain, cultural and religious practices, human rights record, funding, poverty; and COVID-19 Pandemic. The findings of this paper reveals that UN Women plays an important role in advancing gender equality in Nigeria. The paper concludes that institutional structures that hinders the progress of gender equality in Nigeria should be addressed so as to solve the socioeconomic problems that has posed a major threat to the UN women programmes and works. This, the paper recommends that a lot can be achieved by creating institutions and implementing policies that encourage and drive economic growth among women in the country. Domesticating international conventions and eliminating discriminatory laws against women in the Nigerian constitution will also help address the challenges of the UN Women in Nigeria.